Preferred Attributes for Sustainable Wetland Management in Mpologoma Catchment, Uganda: A Discrete Choice Experiment - Jackson Bunyangha; Agnes. W. N. Muthumbi; Anthony Egeru; Robert Asiimwe; Dunston W. Ulwodi; Nathan. N. Gichuki; Mwanjalolo. J. G. Majaliwa (Land, 2022)
Sustainable wetland management is a focus of many countries worldwide. These mainly use protection as a key policy directive for conservation. However, avoidance directives tend to disenfranchise local populations. Thus, such management is often resisted and rarely effective. Tailoring management strategies to user preferences allows conservation to support community livelihoods for sustainable development. This study employed a discrete choice experiment to determine the wetland management attributes preferred by residents of Mpologoma catchment as a prelude to developing a co-management system. Listed in descending order, attribute preferences were paddy farmers’ schemes, fish farming, education and research, protected wetland area, and recreation and tourism. Respondents’ characteristics influenced their choices. Older adults were more likely to support fish farming. In contrast, existing paddy farmers tended to resist such focuses and an increase in protected wetland area. Additionally, respondents with higher education were opposed to paddy farmers’ schemes, and the preference for education and research was positively influenced by respondents’ income. Respondents were willing to pay between $0.64 and $1.76 per household for each unit improvement in the preferred attribute. Our results underscore the role of DCEs in unlocking individuals’ attribute preferences, whose integration into co-management systems can be important for sustainable wetland conservation.